EP172/#350 Integrated molecular profile of platinum resistant epithelial ovarian carcinoma. (4th December 2022) - Seborova, Karolina; Hlavac, Viktor; Holy, Petr; Bjørklund, Sunniva; Fleischer, Thomas; Spalenkova, Alzbeta; Rob, Lukas; Hruda, Martin; Cernaj, Petr; Bouda, Jiri; Kristensen, Vessela N; Soucek, Pavel; et al.
Abstract : Objectives: Epithelial ovarian carcinoma (EOC) is a serious malignancy with high mortality due to late diagnosis and drug resistance development. Drug resistance is one of the major obstacles to successful anticancer therapy. The main aim of our study was to analyze molecular profile based on gene expression, DNA methylation level, and genetic variability in EOC patients stratified by the platinum therapy resistance status. Methods: For the present study, we selected 72 EOC patients with sensitive (N=43) or resistant (N=30) status. Whole genome expression of protein-coding genes was profiled by mRNA sequencing technology (N=60), lncRNA expression by whole transcriptome RNA sequencing (N=23), global methylation by DNA microarrays (N=50), and somatic mutation rate by whole exome sequencing (N=50). Results: Molecular profile of platinum resistant EOC patients differed from sensitive EOC patients in upregulation of five protein-coding genes (NEURL1, FCGBP, MMP11, NCAM1, and ARMC3) and five lncRNA (ADAMTS9-AS1, TCF21-AS1, ARMC3-AS1, LINC-HIST2H3PS2–35, and LINC-BCR-4), higher methylation of seven protein-coding genes (ABCC4, ABCB10, SLC1A7, SLC19A2, SLC50A1, XPC, and FOXO1) and three lncRNA (LIN00263, LINC00460, NEAT1) and higher frequency of mutations in TP53 gene. On the other hand, three protein-coding genes (LPL, CD36, FABP4), and three lncRNA (LINC-IGGL5, LINC-TMEM121–12, CHST6-AS1) were downregulated, lower methylation was observed for ATP1A1 gene, and the Hippo pathway genes were less mutated in resistant patients. Conclusions: Our study shows a complex network of dysregulated genes and gene expression products connected with the resistance status of EOC patients which should be further characterized. Supported by INTER-ACTION LTAUSA19032, GACR no. 21–14082S, AZV no. NU20–09–00174 and GAUK no.1074120.